Soil mites of the families Ascidae, Blattisociidae and Melicharidae (Acari: Mesostigmata) from mountainous areas of Colombia - Rueda-Ramírez, Diana; Varela, Amanda; Moraes, Gilberto J. De (Zootaxa, 2016)
Soil mites of the Ascidae sensu Lindquist & Evans (1965) are poorly known in Colombia. This group, presently represented by the families Ascidae sensu stricto, Blattisociidae and Melicharidae, contains species known to prey on small arthropods and nematodes, thus having the potential to be used for the control of soil pests. The aim of this study was to identify species of this group from a fragment of Andean forest and a nearby grassland at the municipality of La Calera, Cundinamarca Department, Colombia, at about 2800 m of elevation. Nine species were found, including five new species, namely Gamasellodes andinus sp. nov., Gamasellodes intermedius sp. nov., Protogamasellus caleraensis sp. nov., Cheiroseius mesae sp. nov. and Proctolaelaps colombianus sp. nov. Morphological characterisation of all the species and relevant soil characteristics of the sites where the mites were collected are presented.